CD44 as a Potential Screening Marker for Preliminary Differentiation Between Congenital Dyserythropoietic Anemia Type II and Hereditary Spherocytosis. Issue 2 (23rd November 2016) - Singleton, B. K.; Ahmed, M.; Green, C. A.; Heimpel, H.; Woźniak, M. J.; Ranjha, L.; Seeney, F.; Bomford, A.; Mehta, P.; Guest, A.; Mushens, R.; King, M.‐J.
Abstract : Background: Bone marrow examination has been the confirmatory test for congenital dyserythropoietic anemia type II (CDAII). Occasional spherocytes on peripheral blood smear can confound the diagnosis. Since a screening test is still unavailable, we explored the feasibility of using flow cytometry as a preliminary screening method. Methods: Thirteen monoclonal antibodies with specificities for eight erythrocyte membrane proteins were used in FACS analysis to probe the cellular features of red cells from CDAII, normal adults, hereditary spherocytosis (HS), and cord red cells. Confocal microscopy was performed on normal and CDAII to determine the overall distribution of CD44 and CD47. Their expression levels on cultured erythroblasts were also analyzed. Results: The densely stained band 3 as seen in CDAII in gel electrophoresis was also obtained for Dantu phenotype. Likewise analysis of CDAII cases ( n  = 26) using the eosin‐5′maleimide (EMA) binding test found 57% of patients giving results either positive or in the grey area for HS. Enhanced fluorescence of CD44 was detected in 96% of the CDAII patients, and anti‐CD47 binding was also elevated to a lesser degree. Although RNA expressions of CD44 and CD47 in the cultured erythroblasts of normal controls and CDAII were similar, confocal microscopy revealed more CDAII red cells giving elevated fluorescence than normal red cells. Conclusions: A distinction between CDAII and HS can be made using the EMA Binding test and anti‐CD44 binding. Confirmation of CDAII can subsequently be made based on clinical presentation together with either bone marrow examination or DNA sequencing of SEC23B . © 2016 International Clinical Cytometry Society